A pyrane based fluorescence probe for noninvasive prediction of cerebral β-amyloid fibrils. Issue 20 (15th October 2015) - Cheng, Yan; Zhu, Bi-yue; Li, Xue; Li, Guo-bo; Yang, Sheng-yong; Zhang, Zhi-rong
Graphical abstract